A completely randomized experimental design with 3 factors on tempe resistance - Afifah Dilla Indrawati Haryono; Atika Nurani Ambarwati (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Tempe produced in Indonesia generally uses soybeans fermented with microorganisms as the main raw material. This fermented food is liked by many people from various levels of society because of its taste and protein and carbohydrate content. However, tempe can only last for 1-2 days. The average per capita consumption of tempe per week in 2023 increased by 0.143 kg from the previous year. The Central Statistics Agency revealed that the supply of around 335 thousand tons of local soybeans from 2.7 million tons of national soybean needs. The need for soybeans for tempe reaches 70% of the total national need, further strengthening the fact that the amount of local soybeans is decreasing so that the country must import to meet the supply of soybean needs. In the city of Semarang, tempe is made from imported soybeans. Course, other types of local beans are substitutes. The demand for tempe production continues to increase, but some producers have not been able to maintain the quality and durability of tempe. The 3-factor design helps to determine the treatment factors that affect the durability of tempe. Based on the experiment, the durability of tempe was influenced by factors of beans, inoculum, fermentation, bean-inoculum interaction, beans-fermentation, and beans-inoculum-fermentation. Cowpea tempe with yeast inoculum fermented for 24 hours had the best durability